Młodość w procesach wchodzenia w dorosłość. Refleksje z perspektywy przemian przebiegu życia = Youth in the processes of transition to adulthood. Reflections from the perspective of changes in life course patterns - Krzaklewska, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to reflect on the concept of youth in the context of changes in life course patterns. The extension of the process of transition to adulthood has resulted in the conceptualisation of a new phase in the life course - youth - or emerging adulthood. Using autobiographical in-depth interviews with young adults born in the early 1980s, the author discusses ways of defining youth. How do young people understand, experience and position it in relation to adulthood? The researched boom generation of the 1980s in Poland made a life course revolution, prolonging the transition to adulthood and creating new life course patterns. As the analyses show, youth is a significant period or biographical moment for some of the respondents, while at the same time it remains a value or lifestyle not necessarily related to age.
Keywords: młodość; wchodzenie w dorosłość; przebieg życia; youth; transition to adulthood; life course; emerging adulthood; Poland; Polska